Layer-By-Layer Fabrication of Large and Thick Human Cardiac Muscle Patch Constructs With Superior Electrophysiological Properties - Pretorius, Danielle; Kahn-Krell, Asher M.; Lou, Xi; Fast, Vladimir G.; Berry, Joel L.; Kamp, Timothy J.; Zhang, Jianyi (Frontiers in Cell and Developmental Biology, 2021)
Engineered cardiac tissues fabricated from human induced pluripotent stem cells (hiPSCs) show promise for restoring function in infarcted left ventricular (LV) myocardium. For these constructs to reach their clinical potential, they need to be of a clinically relevant volume and thickness, and capable of generating synchronous and forceful contraction to assist the pumping action of the recipient heart. Design requirements necessitate a structure thickness sufficient to produce a useful contractile force, prevascularization to overcome diffusion limitations and sufficient structural development to allow for maximal cell communication. Previous attempts to meet these requirements have been hampered by diffusion limits of oxygen and nutrients (100-200 μm) resulting in necrotic regions. This study employs a layer-by-layer (LbL) fabrication method to produce cardiac tissue constructs that meet these design requirements and mimic normal myocardium in form and function. Thick (> 2 mm) cardiac tissues created from human induced pluripotent stem cell-derived cardiomyocytes, endothelial cells and fibroblasts were assessed, in vitro, over a 4-week period for viability (< 6 % necrotic cells), cell morphology and functionality. Functional performance assessment showed enhanced t-tubule network development, gap junction communication as well as previously unseen, physiologically relevant conduction velocities (> 30 cm/s). These results demonstrate that LbL fabrication can be utilized successfully in creating prevascularized, functional cardiac tissue constructs from hiPSCs for potential therapeutic applications.